Enhancing Entrepreneurial Self-Efficacy among Young Indonesian University Students: The Influence of Entrepreneurial Knowledge, Family Environment, and Entrepreneurial Interest - Prabandari, Sri Palupi; Yulianti, Ida; Barinta, Dunga Dwi (Jurnal Pendidikan Progresif, 2024)
Abstract: Enhancing Entrepreneurial Self-Efficacy among Young Indonesian University Students: The Influence of Entrepreneurial Knowledge, Family Environment, and Entrepreneurial Interest. Objective: This research delves into the complex interplay between Entrepreneurial Knowledge, family environment, and entrepreneurial interest, examining their collective impact on the formation of Entrepreneurial Self-Efficacy (ESE) among aspiring young Indonesian entrepreneurs. Methods: The study focuses on a sample of university students in the city of Malang who exhibit a keen interest in entrepreneurship. A structured survey was administered to 230 carefully selected respondents from various universities in Malang, capturing nuanced insights into their Entrepreneurial Knowledge, family dynamics, entrepreneurial interest, and ESE levels.  Utilizing Structural Equation Modeling (SEM) with SmartPLS 3 software, the collected data underwent rigorous analysis, revealing significant patterns and relationships. The utilization of a quantitative approach and the specific focus on university students in Malang with entrepreneurial aspirations ensure a comprehensive examination of the factors influencing ESE within this particular demographic context. Findings: The findings illuminate the pivotal roles of Entrepreneurial Knowledge, family environment, and entrepreneurial interest in shaping ESE among budding Indonesian entrepreneurs. Specifically, the findings indicate that Entrepreneurial Knowledge, family environment, and entrepreneurial interest exert substantial and positive effects on the development of ESE. Conclucions: In conclusion, this study highlights the critical importance of targeted interventions aimed at enhancing Entrepreneurial Knowledge, cultivating supportive family environments, and stimulating entrepreneurial interest among young individuals aspiring to embark on entrepreneurial ventures. By recognizing and addressing these key determinants, policymakers, educators, and stakeholders can effectively bolster the ESE of young prospective entrepreneurs in Indonesia. Moreover, this research sets the stage for future investigations to delve deeper into the nuanced mechanisms underlying these relationships and to explore additional variables that may further enrich our understanding of ESE formation among youth entrepreneurs.Keywords: entrepreneurial self-efficacy, entrepreneurial knowledge, family environment, entrepreneurial interest.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202429